2018
DOI: 10.1007/s12088-018-0749-6
|View full text |Cite
|
Sign up to set email alerts
|

Dark Septate Root Endophytic Fungus Nectria haematococca Improves Tomato Growth Under Water Limiting Conditions

Abstract: The ascomycetous dark septate endophytic (DSE) fungi characterized by their melanized hyphae can confer abiotic stress tolerance in their associated plants in addition to improving plant growth and health. In this study inoculation of the DSE fungus Berk.& Broome significantly improved all the plant growth parameters like the plant height, stem girth, leaf characteristics and plant biomass of drought-stressed tomato. Root characters like the total root length, primary root diameter, 2nd order root number and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Indeed, in our study, we observed elevation of K and N levels associated with increases of approximately 20% in the total leaf area. This positive effect of fungal DSE isolates on the leaf area was previously observed by other studies [54,90].…”
supporting
confidence: 87%
“…Indeed, in our study, we observed elevation of K and N levels associated with increases of approximately 20% in the total leaf area. This positive effect of fungal DSE isolates on the leaf area was previously observed by other studies [54,90].…”
supporting
confidence: 87%
“…Here, inoculation with PC, EG, DA, PT and AV 2 increased the proline content of I. indigotica compared to that of control plants, suggesting that the inoculated plants had a higher osmotic adjustment capacity under drought stress. Valli and Muthukumar (2018) found that DSE inoculation could enhance proline accumulation in tomato shoots under water-limited conditions. These results indicate that DSE inoculation can regulate proline accumulation to facilitate osmotic regulation, leading to enhanced tolerance to dehydration under water deficits (Hosseini et al 2017;Zang et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Ramy et al (2020) found that metabolites of Cladosporiumin can effectively inhibit pathogenic microorganisms. Nectria haematococca can signi cantly improve plant growth parameters and promote plant growth under abiotic stress (Prema et al, 2018). Enrichment for Lecanicillium, Novosphingobium, Cladosporium, Cordycipitaceae and Nectria may be caused by a better growth performance in Victoria than in the two other.…”
Section: Discussionmentioning
confidence: 99%